Effect on Clinical Outcome and Growth Factor Synthesis With Adjunctive Use of Pulsed Electromagnetic Fields for Fifth Metatarsal Nonunion Fracture: A Double-Blind Randomized Study. (September 2016) - Streit, Adam; Watson, B. Collier; Granata, Jaymes D.; Philbin, Terrence M.; Lin, Hsuan-Ni; O'Connor, J. Patrick; Lin, Sheldon
Background: Electromagnetic bone growth stimulators have been found to biologically enhance the bone healing environment, with upregulation of numerous growth factors. The purpose of the study was to quantify the effect, in vivo, of pulsed electromagnetic fields (PEMFs) on growth factor expression and healing time in fifth metatarsal nonunions. Methods: This was a prospective, randomized, double-blind trial of patients, cared for by 2 fellowship-trained orthopedic foot and ankle surgeons. Inclusion criteria consisted of patients between 18 and 75 years old who had been diagnosed with a fifth metatarsal delayed or nonunion, with no progressive signs of healing for a minimum of 3 months. Eight patients met inclusion criteria and were randomized to receive either an active stimulation or placebo PEMF device. Each patient then underwent an open biopsy of the fracture site and was fitted with the appropriate PEMF device. The biopsy was analyzed for messenger-ribonucleic acid (mRNA) levels using quantitative competitive reverse transcription polymerase chain reaction (QT-RT-PCR). Three weeks later, the patient underwent repeat biopsy and open reduction and internal fixation of the nonunion site. The patients were followed at 2- to 4-week intervals with serial radiographs and were graded by the number of cortices of healing. Results: All fractures healed, with an average time to complete radiographic union of 14.7 weeks and 8.9 weeks for the inactive and active PEMF groups, respectively. A significant increase in placental growth factor (PIGF) level was found after active PEMF treatment ( P = .043). Other factors trended higher following active PEMF including brain-derived neurotrophic factor (BDNF), bone morphogenetic protein (BMP) -7, and BMP-5. Conclusion: The adjunctive use of PEMF for fifth metatarsal fracture nonunions produced a significant increase in local placental growth factor. PEMF also produced trends toward higher levels of multiple other factors and faster average time to radiographic union compared to unstimulated controls. Level of Evidence: Level I, prospective randomized trial.